Sistem Pendukung Keputusan Pemberian Bantuan Sosial Menggunakan Metode Topsis (Studi Kasus SMA Pramula) - Anis, M.Daffa Arief Yudhistira; Saputra, Andri; Khotop, Khotop (MDP Student Conference, 2024)
Pramula High School is one of the schools in the city of Palembang. Many of the students at this school are economically disadvantaged, Pramula High School and the Pramula Foundation provide social assistance to less fortunate students. However, the assessment process is still carried out manually which takes a long time and the assessment results can still be manipulated by irresponsible individuals so that the provision of assistance is not on target to those in need. The aim of this research is to create a decision support system for providing assistance. which can provide fair results as an assessment for providing assistance so that it is right on target and shortens the calculation process, creating a system using the TOPSIS method as a calculation method, the prototype method is used as a system development method. The results of this TOPSIS calculation will produce fair values ​​and values ​​that have been sorted from largest to smallest. The system can provide accurate score results and cannot be manipulated so that schools can provide social assistance on target.